Challenges raising a gifted child: Stress and resilience factors within the family. (May 2017) - Renati, Roberta; Bonfiglio, Natale Salvatore; Pfeiffer, Steven
The research on families of the gifted is extremely limited. In the past, families of the gifted have been studied mainly for two reasons: to discover how family life creates or supports giftedness or eminence, or to understand how one gifted child affects siblings. Few studies, however, have examined the impact of gifted children on the lives of parents. Most studies highlight that many gifted have unique needs and vulnerabilities. Although there is limited empirical research on the experience of parenting a gifted child, there is clinical and anecdotal evidence that the role presents unique parenting challenges. This article presents preliminary research data on the experiences of parenting a gifted child within the family. The authors embrace a risk and resilience model, supported by clinical data obtained from families with a gifted child seen at a leading center for gifted children in Milan.